An Unprecedented Case of p190 BCR-ABL Chronic Myeloid Leukemia Diagnosed during Treatment for Multiple Myeloma: A Case Report and Review of the Literature - Kosuke Miki; Naoshi Obara; Kenichi Makishima; Tatsuhiro Sakamoto; Manabu Kusakabe; Takayasu Kato; Naoki Kurita; Hidekazu Nishikii; Yasuhisa Yokoyama; Mamiko Sakata-Yanagimoto; Yuichi Hasegawa; Shigeru Chiba (Case Reports in Hematology)
We report the case of a 76-year-old man who was diagnosed as having chronic myeloid leukemia (CML) with p190 BCR-ABL while receiving treatment for symptomatic multiple myeloma (MM). The diagnosis of MM was based on the presence of serum M-protein, abnormal plasma cells in the bone marrow, and lytic bone lesions. The patient achieved a partial response to lenalidomide and dexamethasone treatment. However, 2 years after the diagnosis of MM, the patient developed leukocytosis with granulocytosis, anemia, and thrombocytopenia. Bone marrow examination revealed Philadelphia chromosomes and chimeric p190 BCR-ABL mRNA. Fluorescence in situ hybridization also revealed BCR-ABL-positive neutrophils in the peripheral blood, which suggested the emergence of CML with p190 BCR-ABL. The codevelopment of MM and CML is very rare, and this is the first report describing p190 BCR-ABL-type CML coexisting with MM. Moreover, we have reviewed the literature regarding the coexistence of these diseases.